The potential of cement stabilization in soft soil - Nur Diyana, Nordin (2010)
Soft soils often cause difficulties in construction, operation with their low strength and low stiffness nature. However, the engineering properties of these soils can be enhanced by soil stabilization. This research was carried out to study the potential of cement (OPC) stabilization in soft soil around the area of Pekan, Pahang. The objectives of this research are firstly to determine engineering properties of soft soil. The soil was classified as clay with very high plasticity (CV), having liquid limit, plastic limit., plastic index and shrinkage limit of 72.0%, 31.36%, 40.64%, and 7.86% respectively, specific gravity was 2.51 and maximum &y unit weight and optimum moisture content of 14.45kN/m3 and 20.0% respectively. Secondly, to compare the strength and characteristic of soft soil before and after treating with different range of cement concentration, ranging from 2% to 12% of weight of soil. Compaction test was applied to determine the maximum dry unit weight and the optimum moisture content of the soils. From this testing, the maximum dry unit weight was obtained for sample with 10% cement added. By compaction test with mixing water content of 401/o the samples for triaxial test (Unconsolidated Undrained Test) were prepared and then cured in water for 0, 1,7 and 28 days respectively to allow for investigation of the curing effect. The result showed the shear stress is increasing proportional to the cement ratio within curing period. The maximum shear stress was observed for samples with 10% cement added. Oedometer test was carried out to examine the relationship between void ratio and applied pressure to the soil sample. From this test, it showed that 4% and 6% of cement content in the soil were effective in decreasing the settlement of the originally weak soil or another word, increasing the applied pressure to the soil samples would decreases the void ratio of the soil samples. For overall, 10% of cement content shows the effective amount cement added in soft soil stabilization and the objective of this research was achieved.